Thermoelectric Generator for the Recovery of Energy from the Low-Grade Heat Sources in Sugar Industry - Weera Punin; Somchai Maneewan; Chantana Punlek (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In the current work, a thermoelectric power generation system was designed for an assessment of opportunities in terms of electricity production through the utilization of waste heat from sugarcane industries. In this study, the thermoelectric cooling of TEC1-12708T200 was appropriate for use in electric power generation from low-grade heat sources. The experiments used ten thermoelectric modules and an aluminum water block installed on the exterior surface area of a sugar boiler to achieve the same water flow as a traditional system. The results revealed that the power generation system could generate about 30 W (25.7 V, 1.17 A) at a matched load of approximately 36.8 Ω. The thermoelectric power generation system could convert 12.5% of heat energy into electrical energy. Therefore, the thermoelectric power generation system designed in this study could be an effective alternative for waste heat recovery in sugarcane industries.